2005
DOI: 10.1073/pnas.0409541102
|View full text |Cite
|
Sign up to set email alerts
|

Genomic imprinting recapitulated in the human β-globin locus

Abstract: A subset of genes in mammals are subject to genomic imprinting. The mouse H19 gene, for example, is active only when maternally inherited and the neighboring Igf2 gene is paternally expressed. This imprinted expression pattern is regulated by the imprinting control region (ICR) upstream of the H19 gene. A maternally inherited H19 ICR inhibits Igf2 gene activation by the downstream enhancer due to its insulator function while it suppresses H19 gene transcription by promoter DNA methylation when paternally inher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
60
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(70 citation statements)
references
References 30 publications
8
60
2
Order By: Relevance
“…In support of this idea, Davis et al reported that after methylation is erased in migrating and early colonizing primordial germ cells, the DMD and PP regions are methylated asynchronously in the male germ line, with the paternal allele acquiring methylation prior to the maternal allele (6,7). Additionally, in a study in which the DMD was inserted at the AFP locus (32) and in a second experiment inserting the DMD within a human ␤-globin transgene (48), the DMD was unmethylated in spermatozoa but acquired paternal-allele-specific methylation after implantation. Thus, while these studies indicate that the DMD functioned as a methylation-sensitive and maternal-allele-specific insulator at an exogenous locus, it is not clear if the exogenous DMD recapitulated the paternal-allele-specific silencing function.…”
Section: Molecular Analyses Of the Endogenous Wild-type And Mutantmentioning
confidence: 83%
“…In support of this idea, Davis et al reported that after methylation is erased in migrating and early colonizing primordial germ cells, the DMD and PP regions are methylated asynchronously in the male germ line, with the paternal allele acquiring methylation prior to the maternal allele (6,7). Additionally, in a study in which the DMD was inserted at the AFP locus (32) and in a second experiment inserting the DMD within a human ␤-globin transgene (48), the DMD was unmethylated in spermatozoa but acquired paternal-allele-specific methylation after implantation. Thus, while these studies indicate that the DMD functioned as a methylation-sensitive and maternal-allele-specific insulator at an exogenous locus, it is not clear if the exogenous DMD recapitulated the paternal-allele-specific silencing function.…”
Section: Molecular Analyses Of the Endogenous Wild-type And Mutantmentioning
confidence: 83%
“…The recent discovery that Xist becomes biallelically expressed in the inner cell mass of the mouse substantiates the claim that imprinting may not be maintained as once thought (Okamoto et al 2004). A transgenic human β-globin locus has also been shown recently to acquire methylation imprinting during the post-fertilisation period (Tanimoto et al 2005). It is possible that imprints are erased following fertilisation and re-established too rapidly to have been discovered in the murine model system or that genomic imprinting is differentially regulated between species.…”
Section: Genomic Imprinting Statusmentioning
confidence: 88%
“…However, several studies suggest that this key step can be by-passed, and that methylation imprints can be acquired later in development. For instance, when the H19 DMR is inserted at ectopic positions in the genome, paternal-specific DNA methylation at this DMR can be established partially, or even completely, after fertilisation, during early development (Park et al 2004, Tanimoto et al 2005. Furthermore, methylation imprints at some ICRs can be present in a stochastic manner in some embryos derived from DNMT3L-deficient oocytes (Arnaud et al 2006).…”
Section: Imprinting In the Absence Of Germline Dna Methylation Acquismentioning
confidence: 99%